EVALUATION AND DINAMICS OF AIRWAY OBSTRUCTION IN PATIENTS WITH CHRONIC DESTRUCTIVE PULMONARY TUBERCULOSIS BEFORE AND AFTER TREATMENT - JEYHUN M. Ismailzade; RAFIQ I. Bayramov; URFANA B. Nagieva; IRADA M. Akhundova (Фундаментальная и клиническая медицина)
Aim. To study changes in bronchial patency and their correlation to initial manifestations of airway obstruction (AO) and to the rate of clinical and X-ray progression of tuberculosis (TB) in patients with chronic destructive pulmonary tuberculosis (CDP-TB). Materials and Methods. 117 patients with СDP-TB have been subjected to in-depth examination including specially designed questionnaire, physical examination, and spirometry along with bronchodilator test. Resistance to anti-tuberculosis drugs was determined by conventional bacteriological techniques, BACTEC MGIT 960 system, Hain test, and GeneXpert system.Results. Administered therapy improved bronchial patency only in 37,5% of patients with CDP-TB and AO. Such functional changes were more frequently observed in patients with initially minor or moderate obstructive disorders and correlated to the amelioration of clinical or X-ray course of TB. Conclusion. Improvement in bronchial patency can be considered as a therapeutic marker in patients with CDP-TB and AO, highlighting the need in the monitoring of respiratory function and timely prescription of bronchodilators.